European Congress of Physical Education (Fiep Bulletin - online, 2015)
The Physical Education Study Centre of Bologne organizes, under the auspices of the ministry of Education and the University of Bologne, an European Congress od Physical Education to commemorate the 10th anniversary of its foundation.